Correlation between serum ferritin in early pregnancy and hypertensive disorders in pregnancy - Fang, Zhuanji; Zheng, Shuisen; Xie, Yi; Lin, Shunhe; Zhang, Huale; Yan, Jianying (Frontiers in Nutrition, 2023)
Objective: To explore the correlation between serum ferritin (SF) in early pregnancy and the risk of hypertensive disorders in pregnancy (HDP). Method: A retrospective cohort study was conducted on 43,421 pregnant women with singleton pregnancies who underwent antenatal checkups at Fujian Provincial Maternal and Child Health Hospital from January 2018 to December 2020. Based on pregnancy records, women were classified as non-hypertensive, having gestational hypertension, preeclampsia and preeclampsia with severe features according to the degree of the disease. General baseline data, and SF levels in the early (up to 12 gestational weeks) and late (after 28 weeks of gestation) stages of pregnancy were collected. The significance of the characteristic variables was assessed using a random forest algorithm, and the correlation between early pregnancy SF levels and the incidence of HDP was further analyzed using logistics regression adjusted for confounders. A generalized additive model (GAM) was fitted to a smoothed graph of the relationship between early pregnancy SF levels and HDP, and a threshold effect analysis was performed to find the threshold values of early pregnancy SF for iron supplementation therapy. Result: A total of 30,703 pregnant women were included. There were 1103 women who were diagnosed with HDP. Of them, 418 had gestational hypertension, 12 had chronic hypertension without SPE, 332 - preeclampsia and 341 women had preeclampsia with severe features. Levels of SF in early and late pregnancy were significantly higher (P<0.001) in women with HDP compared to non-hypertensive women and the difference was more pronounced in early pregnancy. The random forest algorithm showed that early pregnancy SF was more effective in predicting HDP compared to late pregnancy SF levels and was also an independent risk factor for HDP (adjusted odds ratio (AOR)= 1.07, 95% CI [1.05,1.09]) after correction for confounding factors. Early pregnancy SF >64.22 mg/L was associated with higher risk of developing hypertensive disorders. Conclusion: Risk of pregnancy-related hypertensive disorders increases with increasing early pregnancy SF levels. SF levels may therefore be used to further develop guidelines for iron supplementation therapy in pregnant women.